GUIA SOBRE CIBEREDUCAÇÃO E DIREITOS HUMANOS (CIPEEX, 2026)
This paper addresses the challenges and limits of using technologies in the processing of personal data in light of the General Data Protection Law (LGPD), with special attention to the risks associated with the indiscriminate provision of personal information in everyday situations, such as the use of CPF for discounts in commercial establishments. The research analyzes the ethical, social, and legal implications of the massive collection and use of data, highlighting the importance of cyber education as an essential tool for raising public awareness regarding their fundamental rights, such as privacy, informational self-determination, and the protection of intimacy. The proposal also investigates the role of the National Data Protection Authority (ANPD) and the need for complementary regulations to ensure the effective application of the LGPD in civil environments. The methodology includes a literature review and a critical analysis of common practices in contemporary society that involve the handling of personal data. The work aims to propose educational guidelines and public policies that strengthen the culture of data protection in Brazil, promoting citizen awareness of the challenges of the digital world.Author: Aline Vitória Machado; Co-author: Bruna Gonçalves Nascimento; Advisor: Fabiana Savine Bernardes Pires de Almeida Resende.
Keywords: proteção de dados; LGPD; cibereducação; privacidade; direitos fundamentais